Industrial Relations Theory and Practice: A Note - Clarke, Oliver (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1987)
After having noted the mutual incomprehension between theoritician and practitioners, the author proposes specific areas on which useful work could be completed.